Extrapulmonary lymphangioleiomyomatosis: a wolf in sheep's clothing. Issue 1 (3rd August 2012) - Derweduwen, Aurélie Maria; Verbeken, Erik; Stas, Marguerite; Verschakelen, Johny; Coolen, Johan; Verleden, Geert; Wuyts, Wim
Abstract : We present a case of a 32-year-old woman who was diagnosed with lymphangioleiomyomatosis (LAM) after detecting a mass in the upper anterior mediastinum. Two years after presentation another metastatic localisation of LAM occurred in the cervical region. With this article we would like to highlight the fact that there are still a lot of unanswered questions, especially regarding the best management of extrapulmonary LAM.